DINAMIKA GENDER DALAM KONTROVERSI LGBT DI INDONESIA: ANALISIS BUDAYA, AGAMA, DAN KEBIJAKAN - Safinah, Safinah (Center for Gender and Children Studies, Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) UIN Sultan Thaha Saifuddin Jambi, 2023)
The controversy regarding LGBT (Lesbian, Gay, Bisexual, and Transgender) in Indonesia reflects the tension between traditional values and modernity, as well as between religious norms and human rights. This article analyzes the factors that influence the views of Indonesian people towards LGBT, including cultural influences, religion, government policies, and the role of mass media. The findings suggest that negative views of LGBT people are influenced by conservative cultural norms and religious teachings that firmly reject homosexuality. In addition, existing government policies and regulations often do not support LGBT rights, and even tend to be repressive. Mass media also contributes to strengthening stigma against LGBT through negative representation. As a result, LGBT individuals in Indonesia often face discrimination and violence, which adversely affects their mental health and well-being. This article concludes the need for a more inclusive and sensitive approach to addressing LGBT-related issues, while respecting the dominant cultural and religious values in society